Spline and Spline Wavelet Methods with Applications to Signal and Image Processing Volume III: Selected Topics - Averbuch, Amir Z.; Neittaanmäki, Pekka; Zheludev, Valery A. (Springer International Publishing : Imprint: Springer, 2019)
This book provides a practical guide, complete with accompanying Matlab software, to many different types of polynomial and discrete splines and spline-based wavelets, multiwavelets and wavelet frames in signal and image processing applications. In self-contained form, it briefly outlines a broad range of polynomial and discrete splines with equidistant nodes and their signal-processing-relevant properties. In particular, interpolating, smoothing, and shift-orthogonal splines are presented. .